Pertimbangan Hakim Mahkamah Syar’iyah Langsa Terhadap Penggunaan Saksi De Auditu Dalam Perkara Perceraian - Christiana, Arin (State of Islamic Institute Langsa, 2018)
Witness is a person who gives a statement in the court that qualify the certain conditions about an event or situation that he sees, hears and experiences himself as the evidence has occured  an event or situation. Yet, How if the witnesses collected do not see or experience the incident directly but they only heard from someone else. In The positive legal terms, the witness is called testimonium de auditu, according to Islamic procedural law it is called syahadah al-istifadhah. In the process of how strength the legal evidence of the testimonium de auditu in a divorce case in the Langsa City Syar'iyah Court. Testimonium de auditu in civil procedural law, if it is according to  positive law in article 171 HIR and article 1907 KUH. Civil of testimonium de auditu is not a tool of witness evidence, but it is used as a judge's judgment. But sometimes the exception of testimonium de auditu can be considered from the quality and strength of proof, the application depends on the case. In the perspective of Islamic law, the testimonium de auditu is categorized in the syahadah-istifada as a popular testimony. It means that the testimony delivered has become a public secret, a story in the community, or information in the community about the events that occurred.